PERSEPSI MASYARAKAT SUKU LAUT TENTANG PENDIDIKAN FORMAL DI KAMPUNG PANGLONG, DESA BERAKIT, KABUPATEN BINTAN, KEPULAUAN RIAU - Putriana, Hanifa; Suasti, Yurni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research employs a descriptive qualitative approach, with data collected through in-depth interviews with the Sea Tribe community in Kampung Panglong, Desa Berakit. The results show that the community’s perception of formal education remains low. Formal education is considered less relevant to their tradition as fishermen and does not provide immediate economic benefits, leading many children to drop out of school to help with fishing activities. Factors shaping these perceptions include: (1) limited family economic conditions, with the majority working as fishermen; (2) low parental education levels; (3) traditions and habits that prioritize fishing work; (4) limited educational facilities and infrastructure; and (5) a social environment dominated by mindsets that do not support the importance of education. These findings confirm that the low participation in education among the Sea Tribe community is the result of the interaction of economic, social, cultural, and environmental factors.